Service quality in public universities venezuelan (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
The purpose of this paper is to present the most relevant results of a research therefore seeks to assess the dimensions of quality of service in the public universities located on the east coast of Lake Maracaibo, following the approach of silicon, and González Casares (2000). Theoretical considerations of the construct of quality of service, including Vargas (2007) and Chambers (2004). Methodologically defined as descriptive and field, the population was composed of university teaching staff in public universities on the east coast of Lake Maracaibo, Zulia State, Venezuela, consisting of 96 subjects belonging to the University of Zulia (LUZ) and the Universidad Nacional Experimental "Rafael Maria Baralt (UNERMB), to which were applied a questionnaire with 25 Items 5 alternatives. Among the findings: For the dimension of service quality, delivery time is one of the most critical factors in the satisfaction of service for university teachers, in the quality of human relations, respect the teacher, is considered potential value, the quality in attitudes, shows that staff almost never takes an attitude of approval before the suggestions of teachers and quality in social responsibility is presented as a weakness of university service.
Keywords: quality of service; university teaching; administrative personnel; public university